Census of mental hospital patients and life expectancy of those unlikely to be discharged. Issue 5998 (20th December 1975) - Bewley, T; Bland, J M; Ilo, M; Walch, E; Willington, G
Abstract : A census in a London mental hospital was performed so that the numbers of patients requiring permanent care for the next 20 to 40 years could be estimated. Of 1467 resident patients 20% had been admitted in the preceding five months and 15% in the year before that. Of the 65% who had been in hospital for over 17 months 1% (16 patients) had been in hospital for over 5o years. Altogether 257 (18%) patients would probably be discharged, 339 (23%) might possibly be discharged if there were adequate community facilities, but 871 (59%) were not likely to be discharged; 239 patients under the age of 65 who had been admitted between 1950 and 1973 were unlikely to be discharged. There were about 10 new younger long-stay patients from each year's admissions. Three conditions–schizophrenia, organic brain syndrome, and affective illness–affected 79% of the population. Fourteen per cent had been employed on admission and 28% were considered employable or possibly employable. Half of those who might be considered for discharge (296) would need a hostel. No rehabilitation was needed or possible for 40% of the patients; 299 (20%) patients were chairbound or bedridden and 400 (27%) were totally dependent on nursing and 587 (40%) partly dependent. Twenty months after the census 361 (25%) patients had left (59 had been readmitted), 284 (19%) had died, and 822 (56%) had remained as inpatients. The most realistic future prediction was that 210 (14%) of these patients would still be in the hospital in 20 years and 43 (3%) in 40 years. In the light of these findings and the scarceness of resources current Department of Health and Social Security plans for phasing out mental hospitals must be challenged.